Agribisnis dengan Pendekatan Terpadu - Eko Murdiyanto; Darmadi Darmadi (Jurnal Dinamika Sosial Ekonomi, 2001)
The national agricultural development policy that oriented to agribussines system faced to farmer condition in Indonesia. So, we need farmer function as one of section from "agriculture community with big agribusinessman as a locomotif. With integrated approach farmers can be part of agribusiness sub system that can compete in the grobal market. In addition to the farmers can be a subject of development agribussines system for prevent farmers more left in National development.Keyword: agribusiness system, agribusiness community and Integrated approach.